The Role of Social Commerce in Building Consumer Trust Among Mompreneur Enterprises - Maghfirah Sari Azis; Puji Novita Sari (Jurnal Administrasi Profesional, 2026)
This study aims to examine the role of social commerce utilization in building consumer trust and enhancing business sustainability among mompreneur enterprises in Makassar City, Indonesia. The rapid growth of digital entrepreneurship and social commerce platforms has created significant opportunities for women-led microenterprises; however, maintaining consumer trust remains a critical challenge in online business environments characterized by uncertainty and intense competition. This study employed a quantitative research approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the relationships among Social Commerce Utilization, Consumer Trust, and Business Sustainability. Data were collected through an online questionnaire distributed to 400 mompreneurs actively operating businesses through social commerce platforms such as TikTok Shop, Instagram, WhatsApp Business, Facebook Marketplace, and Shopee Live. The findings revealed that Social Commerce Utilization significantly and positively affected Consumer Trust and Business Sustainability. Furthermore, Consumer Trust was found to significantly influence Business Sustainability and partially mediate the relationship between Social Commerce Utilization and Business Sustainability. The measurement model assessment demonstrated satisfactory reliability and validity, while the structural model showed strong predictive capability and excellent model fit. These findings indicate that social commerce platforms play an important strategic role in strengthening customer trust and supporting sustainable business performance among women-led online microenterprises. This study contributes to the development of social commerce and digital entrepreneurship literature by providing empirical evidence from the context of mompreneur enterprises in emerging digital business ecosystems.